Short‐term intermittent energy restriction interventions for weight management: a systematic review and meta‐analysis. (4th October 2017) - Harris, L.; McGarty, A.; Hutchison, L.; Ells, L.; Hankey, C.
Summary: This systematic review synthesized the available evidence on the effect of short‐term periods of intermittent energy restriction (weekly intermittent energy restriction; ≥7‐d energy restriction) in comparison with usual care (daily continuous energy restriction), in the treatment of overweight and obesity in adults. Six electronic databases were searched from inception to October 2016. Only randomized controlled trials of interventions (≥12 weeks) in adults with overweight and obesity were included. Five studies were included in this review. Weekly intermittent energy restriction periods ranged from an energy intake between 1757 and 6276 kJ/d −1 . The mean duration of the interventions was 26 (range 14 to 48) weeks. Meta‐analysis demonstrated no significant difference in weight loss between weekly intermittent energy restriction and continuous energy restriction post‐intervention (weighted mean difference: −1.36 [−3.23, 0.51], p = 0.15) and at follow‐up (weighted mean difference: −0.82 [−3.76, 2.11], p = 0.58). Both interventions achieved comparable weight loss of >5 kg and therefore were associated with clinical benefits to health. The findings support the use of weekly intermittent energy restriction as an alternative option for the treatment of obesity. Currently, there is insufficient evidence to support the long‐term sustainable effects of weekly intermittent energy restriction on weight management.